1998
DOI: 10.1103/physrevlett.80.1011
|View full text |Cite
|
Sign up to set email alerts
|

Noncoarsening Origin of Logarithmic-Normal Size Distributions during Crystallization of Amorphous Thin Films

Abstract: It is demonstrated that the formation of logarithmic-normal crystallite size distributions during crystallization of amorphous thin films can be a consequence of the dynamics of random nucleation and growth without the involvement of coarsening. Our analytical result is supported by experimentally observed crystallite size distributions during the crystallization of amorphous Si thin films obtained from transmission electron microscopy. [S0031-9007(97)05141-7] The phase transformation from the amorphous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Lognormal size distributions in phase transformations have conventionally been attributed to coarsening [6,7]. Our earlier work [8], however, pointed out that such distributions might occur due to time dependent kinetics of nucleation and growth, without the involvement of coarsening. Literature on nucleation describes the initial or early stages of nucleation [9,10] and there are a number of derivations of nucleation rates for these early stages, see eg.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Lognormal size distributions in phase transformations have conventionally been attributed to coarsening [6,7]. Our earlier work [8], however, pointed out that such distributions might occur due to time dependent kinetics of nucleation and growth, without the involvement of coarsening. Literature on nucleation describes the initial or early stages of nucleation [9,10] and there are a number of derivations of nucleation rates for these early stages, see eg.…”
mentioning
confidence: 98%
“…The corresponding parameter v 0 = 1.72 ± 0.34 µm/h is taken from Ref. [8], which also states the crystallization parameters t 0 = 1.5 ± 0.5h and t c = 4 ± 0.5h, necessary for Eq. (8), using d = 2 for amorphous Si films solid phase crystallized at 600…”
mentioning
confidence: 99%
“…The intrinsic depletion of the nucleation sites during the nucleation and growth leads naturally to a nonlinear effect in the subsequent evolution of the CSD. Although it was suggested that the interplay between the dynamics of nucleation and growth could give rise to a log-normal CSD [8,9], no definite experimental evidence has been obtained excluding involvement of coarsening of the crystallites in the formation process.…”
mentioning
confidence: 99%
“…Bergmann, Shi, and Krinke [1] (BSK) use an analytical description of nucleation and growth to explain the observed grain size distribution in an amorphous Si film. It is shown below, however, that the proposed description does not produce the known limit of transient nucleation which arises for a negligible crystallization fraction, X͑t͒ (and which corresponds to t c !`in Eq.…”
mentioning
confidence: 99%
“…(4) of BSK should have a different form [5(b)] (again, Bergmann, Shi, and Krinke [1] miss a large logarithmic term). On the other hand, the reported experimental depletion of 2.8% is remarkably small.…”
mentioning
confidence: 99%